Tau-dependent HDAC1 nuclear reduction is associated with altered VGluT1 expression - Siano, Giacomo; Madaro, Giuseppe; Caiazza, Maria Claudia; Allouch, Awatef; Varisco, Martina; Mignanelli, Marianna; Cattaneo, Antonino; Di Primio, Cristina (Frontiers in Cell and Developmental Biology, 2023)
During AD pathology, Tau protein levels progressively increase from early pathological stages. Tau altered expression causes an unbalance of Tau subcellular localization in the cytosol and in the nuclear compartment leading to synaptic dysfunction, neuronal cell death and neurodegeneration as a consequence. Due to the relevant role of epigenetic remodellers in synaptic activity in physiology and in neurodegeneration, in particular of TRIM28 and HDAC1, we investigated the relationship between Tau and these epigenetic factors. By molecular, imaging and biochemical approaches, here we demonstrate that Tau altered expression in the neuronal cell line SH-SY5y does not alter TRIM28 and HDAC1 expression but it induces a subcellular reduction of HDAC1 in the nuclear compartment. Remarkably, HDAC1 reduced activity modulates the expression of synaptic genes in a way comparable to that observed by Tau increased levels. These results support a competitive relationship between Tau levels and HDAC1 subcellular localization and nuclear activity, indicating a possible mechanism mediating the alternative role of Tau in the pathological alteration of synaptic genes expression.